A quick & easy guide to asexuality - Muldoon, Molly, 1987-; Hernandez, Will (Limerence Press, an imprint of Oni-Lion Forge Press Publishing Group, LLC, 2022)
"Asexuality is often called The Invisible Orientation. You don't learn about it in school, you don't hear "ace" on television. So, it's kinda hard to be ace in a society so steeped in sex that no one knows you exist. Too many young people grow up believing that their lack of sexual desire means they are broken--so writer Molly Muldoon and cartoonist Will Hernandez, both in the ace community, are here to shed light on society's misconceptions of asexuality and what being ace is really like. This book is for anyone who wants to learn about asexuality, and for Ace people themselves, to validate their experiences. Asexuality is a real identity and it's time the world recognizes it"--